METHODOLOGICAL ASPECTS OF REGIONAL RESEARCHES - Vladeva , Rositsa (Revista Inclusiones, 2020)
In this study, it’s tried to make the connection between the regional paradigm, the spatial approach, localization studies and regional researches clear. It accentuates on the theoretical basis of contemporary methodological aspects and concepts. The authors focused on the principles and the methods for realizing geographical analysis and terrain researches